Penentuan Potensi Sumber Daya Batuan Mangan Menggunakan Metode Geolistrik Tahanan Jenis Konfigurasi Wenner di Buraen, Amarasi Selatan-Kabupaten Kupang - Regina Seran (Fakultas Pertanian, Universitas Timor, 2019)
Geoelectrical resistivity research has been conducted using Wenner Sounding Configuration in Buraen Village South Amarasi district Kupang Regency which covered 2025 m2 area research. The purpose of this research is to determine the spreading pattern and value range of manganese rock resistivity and also calculate the potential resources of manganese rock on that area research. The processing data was used the IP2WIN to compute the depth, thickness, number of layers and also value of rock resistivity. Surfer 9 program was used to compute manganese resources. The result of the research showed that spreading of manganese rock was almost exists all over measurement lines which varies the thickness. Based on rock layer analysis, resistivity values were on the range 4 Ωm – 31,9 Ωm which suspected as manganese rock layers. The volume of manganese rock from the calculation results was 36.707 m3 and it was also hypothetical resources because of geological validity in the survey review.